ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS PENJUALAN KREDIT PADA PT. RAJAWALI NUSINDO CABANG MANADO - Budiman, Nindy Vannesya; Karamoy, Herman; Tirayoh, Victorina Z (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
An internal control system for credit sales is needed to support the continuity operation of the company. By good internal recovery, credit sales activities can avoid the risks that cause losses. The objective of this study is to analyze the internal control system for credit sales applied at PT. Rajawali Nusindo Manado Branch and at the same time determine the system of internal control over credit sales has been well implemented by using descriptive qualitative approach. The analytical method used in this study is descriptive method which describes the results in accordance with those found directly through the process in the field. The result of PT. Rajawali Nusindo Manado Branch shows that the internal control system for credit sales is not being well protected due to a mismatch with some internal control components.